Does satisfaction with amenities and environment influence the taste for revolt in the middle east? - Mohammad Reza Farzanegan; Hassan F. Gholipour (Constitutional Political Economy, 2023)
The purpose of this study is to explore the relationship between individuals' satisfaction with amenities and environmental quality and taste for revolt in the Middle East. Using recent World Value Survey data (WVS7, 2017–2021) from Egypt and Iraq (which have been experiencing severe environmental degradation and inadequate and mismanagement of public infrastructure) and applying Probit regressions, our results show that satisfaction with amenities and environmental quality indicators are negatively and statistically related to individuals' inclination towards revolt in both countries. This finding is more pronounced in urban areas, particularly in large cities. We also find that individuals' satisfaction with amenities and environmental quality affect the taste of revolt through the individual's life satisfaction and satisfaction with the government's provision of utilities. The analysis for Egypt suggests that satisfaction with public transportation systems, roads and highways, air quality, and housing quality are significantly and negatively associated with support for revolutionary action. For the Iraq sample, we find that dissatisfaction with roads and highways, water quality, school quality, and the physical settings of cities lead to a higher probability of support for uprising.
Keywords: D74; H54; Q53; 330; Amenities; Air quality; Middle east; Environment; Pollution; Revolution; Satisfaction